Design of multi‐pad electrotactile system envisioned as a feedback channel for supernumerary robotic limbs. Issue 10 (28th June 2022) - Boljanić, Tanja; Isaković, Milica; Malešević, Jovana; Formica, Domenico; Di Pino, Giovanni; Keller, Thierry; Štrbac, Matija
Abstract: Background: Providing real‐time haptic feedback is an important, but still not sufficiently explored aspect of the use of supernumerary robotic limbs (SRLs). We present a multi‐pad electrode for conveying multi‐modal proprioceptive and sensory information from SRL to the user's thigh and propose a method for stimuli calibration. Methods: Within two pilot tests, we investigated return electrode configuration and active electrode discrimination in three healthy subjects to select the appropriate electrode pad topology. Based on the obtained results and anthropometric data from the literature, the electrode was designed to have three branches of 10 pads and two additional pads that can be displaced over/under the electrode branches. The electrode was designed to be connected to the stimulator that allows full multiplexing so that specific branches can serve as a common return electrode. To define the procedure for application of this system, the sensation, localization, and discomfort thresholds applicable for the novel electrode were determined and analyzed in 10 subjects. Results: The results showed no overlaps between the three thresholds for individual pads, with significantly different average values, suggesting that the selected electrode positioning and design provide a good active range of useful current amplitude. The results of the subsequent analysis suggested that the stimuli intensity level of 200% of the sensation threshold is the most probable value of the localization threshold. Furthermore, this level ensures a low chance (i.e., 0.7%) of reaching the discomfort. Conclusions: We believe that envisioned electrotactile system could serve as a high bandwidth feedback channel that can be easily set up to provide proprioceptive and sensory feedback from supernumerary limbs. Abstract : Based on the pilot tests on return electrode configuration and active electrode discrimination and the anthropometric data from the literature, the novel multi‐pad electrode for the thigh, with three arrays of 10 pads and two additional pads, was designed. Investigation of the electrode calibration procedure (sensation, localization, and discomfort thresholds) showed that the selected electrode positioning and design provide a good active range of useful current amplitude. Subsequent analysis suggested that the stimuli intensity could be set to 200% of the sensation threshold.